Power quality improvement of wind energy system using energy storage model and DSTATCOM - Kishor V. Bhadane; Mohan Thakre; Rakesh Shriwastava; Deepak P. Kadam; Dnyaneshwar V. Bhadane; Mahesh Harne (Institute of Advanced Engineering and Science, 2022)
Nowadays power crises in different countries are observed and the main cause of the power crisis is the huge gap between the supply and demand of electricity, renewable energy sources are identified as an alternative to overcome the power crisis gap. Renewable wind energy is the most promising energy source. Increasing the integration of wind energy into the grid causes the exploitation of power quality. Hence there is a need to deal with this issue. In this case, supercapacitors and custom power devices are introduced as smart energy storage devices in grid-connected wind energy systems for power quality enhancement features. The indirect current control scheme has interfered with custom power devices based on DSTATCOM. The optimal MATLAB-based smart energy storage model and hardware results are compared and validated. power quality improvement feature of grid-connected wind energy system using DSTATCOM is highlighted. The main aim of this study is to determine and interface the optimistic energy storage device into grid connected wind energy system. So that the stability of the wind energy system is to be maintained and also able to enhance the overall efficiency of the wind energy system.